Improving Language Skills and Instilling Character Values in Children Through Storytelling - Huda, Syamsul; Ridwanulloh, M. Ubaidillah; Khasanah, Siti Mauridatul; Prasetiyo, Andika Eko; Donasari, Renita (Universitas Islam Negeri Raden Intan Lampung, 2022)
The purpose of this study is to explain the storytelling method in improving language skills and at the same time instilling character values in children. Character issues in the younger generation are still often encountered both in society and through the news on social media. One solution is to include character values from an early age in kindergarten learning by applying the storytelling method. By taking inspirational stories from characters that contain good character values, children can learn both language skills and character values. The research method used was the Classroom Action Research (CAR) method. Analysis and presentation of data used a qualitative descriptive method. The data were collected through observation, interviews, and documentation. The result of the study showed that the use of storytelling methods in early childhood to improve language and instill character values had a significant effect. The ratio of the pre-test and post-test results showed a significant improvement, it was from 61% to 96%. Character changes in a positive direction appeared such as being honest, responsible, independent, polite, and following parental orders. Furthermore, children were also motivated to learn in improving their language skills such as speaking, listening, reading, and writing which then affected the child's formal language. Thus, the use of the storytelling method in the learning process not only improved language skills but also affected the child's character because presenting true stories from human life provides a good and ideal example for children to instill good character in themselves.